2008
DOI: 10.2355/isijinternational.48.988
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Zinc Ions on Initial Stage of Localized Corrosion of Zn and Zn–Al Alloy Coated Steels with Photon Rupture Method

Abstract: The effect of pre-dissolved Zn ions in the solutions on the initial stage of localized corrosion after oxide films of Zn and Zn-Al alloy coated steels were removed by a photon rupture method, focused pulsed Nd-YAG laser beam irradiation, was investigated electrochemically. Zn ions can be inhibited dissolution of the Zn coated layer by precipitation of zinc hydroxide, which is formed by hydrolysis reaction of dissolved Zn ions in neutral buffer solutions. However, Zn ions do not affect the dissolution of a Zn-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…They 41 also demonstrated that the inhibition of the cathodic reaction can be attributed to the precipitation of zincbased corrosion products on the active cathode. Sakairi et al [42][43][44] reported that the corrosion behavior of steel in aqueous solutions was influenced by Zn 2+ , with a laser irradiation method. Hirasaki et al 45 reported that the anodic current of Fe around the immersion potential decreased with increases of Zn 2+ concentration in acid solutions.…”
mentioning
confidence: 99%
“…They 41 also demonstrated that the inhibition of the cathodic reaction can be attributed to the precipitation of zincbased corrosion products on the active cathode. Sakairi et al [42][43][44] reported that the corrosion behavior of steel in aqueous solutions was influenced by Zn 2+ , with a laser irradiation method. Hirasaki et al 45 reported that the anodic current of Fe around the immersion potential decreased with increases of Zn 2+ concentration in acid solutions.…”
mentioning
confidence: 99%